The moderating influence of supplier culture on the relationship between buyer power and supplier shirking. Issue 3 (3rd April 2022) - Skowronski, Keith; Benton, W. C.; Handley, Sean
Abstract: Globalization has added a layer of complexity to the challenge of mitigating opportunism in buyer–supplier relationships. When engaging with suppliers in different countries, buyers must manage relationships across various cultures. Prior empirical research has shown that inter‐firm power affects opportunism in exchange relationships, and conceptual studies suggest that national culture is a location characteristic that could influence inter‐firm power. However, no research has empirically examined the efficacy of inter‐firm power in controlling opportunism, or other exchange outcomes, across different cultural contexts. To study this relevant issue, we investigate how a supplier's national culture influences the effectiveness of two bases of inter‐firm power, coercive and expert power, on a form of opportunism that has been anecdotally observed in practice—supplier shirking. We utilize primary dyadic data on 109 outsourcing relationships and secondary data of supply chain location characteristics to examine this phenomenon. We find that the effects of inter‐firm power on shirking vary across suppliers in different cultures and that, in certain cultures, coercive power may reduce the effectiveness of expert power. Our results show that manufacturers must explicitly consider suppliers' national culture when managing a globally dispersed supply base or risk encountering supplier shirking. Highlights: While the effectiveness of buyer expert power in reducing supplier shirking is not contingent on the supplier's national culture, buyer coercive power appears to be more detrimental (i.e., supplier shirking increases) when used with suppliers operating in cultures with higher levels of long‐term orientation, collectivism, or power distance. Coercive power is also found to diminish the beneficial effects of buyer expert power in reducing shirking with suppliers operating in high power distance and high uncertainty avoidance cultures. Surprisingly, coercive power is found to strengthen the beneficial effects of buyer expert power in reducing shirking with suppliers operating in low power distance and low uncertainty avoidance cultures.